2013
DOI: 10.4155/fmc.12.206
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Complications and Diabetic Retinopathy: Recent Advances and Future Implications

Abstract: Retinal microvascular alterations have been observed during diabetic retinopathy (DR) due to the retinal susceptibility towards subtle pathological alterations. Therefore, retinal microvascular pathology is essential to understand the nature of retinal degenerations during DR. In this review, the role of retinal microvasculature complications during progression of DR, along with recent efforts to normalize such alterations for better therapeutic outcome, will be underlined. In addition, current therapeutics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 126 publications
0
54
0
1
Order By: Relevance
“…In earlier DR, there is decrease of retinal perfusion caused by the constriction of arterial vasculature retinal and consequent induction of a series of alterations [Barot et al, ]. Thickening of the vascular basal membrane is present due to the alteration of tight junctions, apoptosis of pericytes and endothelial cells, which become the earliest development of histological changes in DR [Alder et al, ].…”
Section: Diabetic Retinopathymentioning
confidence: 99%
“…In earlier DR, there is decrease of retinal perfusion caused by the constriction of arterial vasculature retinal and consequent induction of a series of alterations [Barot et al, ]. Thickening of the vascular basal membrane is present due to the alteration of tight junctions, apoptosis of pericytes and endothelial cells, which become the earliest development of histological changes in DR [Alder et al, ].…”
Section: Diabetic Retinopathymentioning
confidence: 99%
“…With the improvement of people's living standards, the incidence of diabetes has increased in developed and developing countries, including China [ 1 ]. Patients who suffer from diabetes for a long time likely experience chronic vascular injury caused by high blood sugar levels; these patients are also at risk of DR when chronic vascular injury occurs in the retina [ 2 , 3 ]. The pathogenesis of DR is generally divided into two stages, namely, nonproliferative DR (NPDR) and proliferative DR (PDR).…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenesis of DR is generally divided into two stages, namely, nonproliferative DR (NPDR) and proliferative DR (PDR). In early NPDR stage, DR is characterized by retinal blood vessel permeability as a result of damaged blood retinal barrier (BRB); in PDR stage, retinal neoangiogenesis occurs [ 2 , 3 ]. Previous studies have demonstrated that both inflammation and angiogenesis play important roles in regulating the development of DR, and thus anti-inflammation and antiangiogenesis are potential therapeutic strategies for the treatment of DR [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neovascularization is the most common pathology in many blinding disorders including wet age-related macular degeneration (AMD) [1], macular edema (ME) and proliferative diabetic retinopathy (DR) [2]. Retinal microvascular changes have been observed during these complications, which are attributed to retinal vulnerability towards subtle pathological alterations.…”
Section: Introductionmentioning
confidence: 99%